The contextual Teaching And Learning (CTL) Based On Contextual Teaching And Learning (CTL) Based On Student Worksheets - Deni Indriani Tampubolon; Zulfi Amri (Indonesian Journal of Education and Mathematical Science, 2021)
Teaching materials that are too monotonous and have no color in the LKPD which are currently used by many students in schools make students less interested in seeing and even reading them. The purpose of this study is how to design the development and feasibility of student worksheets (LKPD) Mathematics using a contextual teaching learning model on the subject of the Himpunan. Can the developed student worksheets (LKPD) use the contextual teaching learning model on the subject of the Association. This research is a development research (RnD) using a 4-D model, namely the definition stage, the design stage, the develop stage and the dissemination stage. However, it was modified to be 3-D because the application media did not reach the deployment. The research instrument is the RPP feasibility test questionnaire and the LKPD feasibility test questionnaire. Based on the results of expert validation, from the results of the final assessment on RPP validation by the three experts with an average of 4.4 with a percentage of 88.6%, namely the Very feasible category. The results of the final assessment on LKPD validation by the three experts with an average score of 4.5 with a percentage of 87.2%, namely the Very feasible category. Based on these data, it can be concluded that the development of Contextual Teaching Learning (CTL)-Based Student Worksheets on the subject matter of the Association is very feasible to use.